Pengukuran Financial Distress Yang Dipengaruhi Oleh Sales Growth, Kepemilikan Manajerial, Dan Operating Capacity Pada Perusahaan Transportasi Dan Logistik Yang Terdaftar Di Bei Tahun 2018-2022 - Peradana, Mario Seno; Wardoyo, Dwi Urip (eProceedings of Management, 2024)
Financial distress can be experienced by every company, which can be caused by internal or external factors ofthe company. A company may experience financial distress when the condition of the company is unable to meetits financial obligations. If this condition continues, the company will face the risk of bankruptcy due to its inabilityto meet its financial obligations. There are several factors that influence financial distress, namely sales growth,managerial ownership, and operating capacity. This research aims to determine how the simultaneous and partialeffects of the variables of sales growth, managerial ownership, and operating capacity on financial distress intransportation and logistics companies listed on the Indonesia Stock Exchange (IDX) in 2018-2022. The samplingtechnique in this research is purposive sampling, obtaining 105 samples consisting of 21 companies with anobservation period of 5 years. This research uses a quantitative method using panel data regression techniquesprocessed using Eviews 13 software. The results of this study show that: (1) Sales growth, managerial ownership,and operating capacity simultaneously affect financial distress. (2) Sales growth partially does not affect financialdistress. (3) Managerial ownership partially has a negative effect on financial distress. (4) Operating capacitypartially has a positive effect on financial distress. Keywords-financial distress, sales growth, managerial ownership, and operating capacity.